Off-equilibrium kinetic Ising model: The metric case - Luca Di Carlo (Physical Review Research)
We investigate the critical behavior of the kinetic Ising model with nonreciprocal nearest-neighbor interactions. A finite-size scaling study suggests that the model belongs to the Ising universality class. We characterize the off-equilibrium behavior of the model by measuring the entropy production rate and by studying the coarsening dynamics, which shows a superdiffusive relaxation. A coarse-grained equation of motion is in compelling agreement with the numerical findings. A one-loop renormalization group calculation confirms that the model belongs to the model A universality class.